(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2026)
It is evident to all the extent of the importance of studies in political systems as an academic specialization, in providing and enriching knowledge for the Iraqi politician, since these studies are derived from reality and are based on a purely academic methodology, documented through rigorous studies and precise scientific findings. What grants the researcher in political affairs an appropriate intellectual framework is the ability to address unresolved issues in history that some attempt to calculate in isolation, without linking them to other related issues. Today, we seek to identify common ground and to avoid being drawn into self-evident assumptions that occupy a wide space in the escalating political conflict, which in turn emerged within the divided Iraqi society after 2003. This represents an imbalance in the balance of power and a sense of suspicion among other components, which the 2005 Constitution attempted to define indirectly. Methodology and historical determinism thus formed an intense cultural conflict between one side and another, and the political arena became engulfed in a fierce, unrelenting struggle. Political currents confronted one another, each according to its size, and political components emerged aligning themselves with their respective currents and blocs, while researchers found it difficult to identify logical alternatives capable of either mobilizing the street or calming its conflicts. Therefore, we do not stand idly by in the face of overlapping arenas, nor do we allow conflicts—even virtual ones on the internet—to persist. We may record the strengths and weaknesses of one component or another. The country became divided into two camps, with each side considering itself to be right. Ideas and cultures slipped into a state of permanent conflict, which became evident in elections where each component stood with its own, excluding others, recording record numbers in the lexicons of the unconscious. Collective reasoning operated in a rigid manner, attempting to secure a foothold in decisive issues, moreover, the masses were provoked by certain sectarian terms, which one side or another perceived as attempts to undermine it, with each interpreting them as directed against itself and its component. Consequently, the following terms were used in a way that allowed Iraqi politicians to exploit them in their daily dealings, investing them in the worst as follows; Quota-based power sharing was first adopted, and then this term was refined into notions such as partnership, consensus, and balance. Yet, after all this, it entrenched the abhorrent concept of sectarianism. This emerged as a reaction to an authoritarian, totalitarian, and dictatorial regime that divided a single people and fragmented them according to sectarian and regional loyalties. What further compounded the problem was the system that came after 2003, which institutionalized this concept, immersed itself in it, and even took satisfaction in it. Accordingly, the presidencies were distributed on the basis of a sectarian constitutional custom: the President to be Kurdish, the Prime Minister Shiite, and the Speaker of Parliament Sunni, this arrangement extended to all positions within the Iraqi state, reaching even service-level employees. This constitutional custom, although not written into the constitution, had previously been practiced in Lebanon and was later embodied in Iraq. What becomes evident from all this is that any group that had been deprived and whose freedom had been suppressed began to exercise its freedom on a wider scale, Shiites, who had been deprived of practicing their rituals, reclaimed—under the new system of governance—their path toward freedom as a result of the sectarian repression they had endured. The Kurds likewise began to practice their national rituals and to express their national identity openly and explicitly.